Menjadi Calon Guru: Studi Naratif Multitugas Mahasiswa PPL di SMP Negeri 12 Pematangsiantar - Dumaris E. Silalahi; Indah Anastasya Togatorop; Helena Zepania Samosir; Calvyn Sepanya Siregar; Cintya Pinta Nainggolan; Angelina Agustina Br Turnip; Falty Bastian Samosir; Cindy Yani Simorangkir; Kevin Christian Siagian (Young Journal of Social Sciences and Humanities, 2026)
This research aims to describe in-depth the dialectical process of professional identity formation among pre-service teachers through multidimensional involvement in partner schools. Teaching practicum (PPL) is often narrowly perceived as a mere instructional exercise; however, field realities reveal a complex and systemic multidimensional involvement. Utilizing a qualitative method with a narrative inquiry approach, this study explores the subjective experiences of a student teacher at SMP Negeri 12 Pematangsiantar. Data were collected through participant observation, practicum reports, and narrative reflections compiled over a twelve-week period. The results indicate that the student undergoes a process of "becoming a teacher" through a dialectic between the pedagogical idealism of the university and the structural pragmatism of the school. Involvement extending beyond classroom boundaries—encompassing character internalization, administrative management, and learning resource organization—functions as an authentic laboratory for constructing professional identity. The study concludes that multi-tasking demands are not merely technical obstacles but transformative instruments that mature the self-efficacy and ethical commitment of future educators. The implications of this research emphasize the importance of repositioning teaching practicum programs as dynamic spaces for identity negotiation in facing the complexities of the educational ecosystem.